A Drug Utilization Study on Pharmaceutical Preparations for Scabies : The Prevalence of Scabies and its Management - Goto, Nobuyuki; Komoda, Masayo; Nakayama, Kazuhiko; Shiraishi, Tadashi; Sugiyama, Tadashi; Masada, Mikio; Suda, Noriyuki; Yamakawa, Masayuki (Iryo Yakugaku (Japanese Journal of Pharmaceutical Health Care and Sciences), 2003)
In Japan, no report has so far been published which evaluates drug use for scabies. We surveyed the prevalence of scabies and its management. The result showed that scabies is not a rare contagious parasitic skin infection. Since there is no effective and safe drug for scabies on the market, the following medications were found to be used for its treatment : crotamiton (unlabeled use), Benzyl benzoate formulation (compounded), γ-BHC formulation (compounded). Adverse events associated with those drugs were also reported. In most case, the patients did not receive adequate counseling regarding their drug therapy. Physicians and other health care professionals have been frustrated by the lack of effective preventive and therapeutic intervention for scabies. It is therefore necessary to approve a drug to treat scabies and to also establish clear guidelines for the treatment and management of scabies.